Sensory characteristics of chronic non-specific low back pain: A subgroup investigation - O'Sullivan, Peter; Waller, Robert; Wright, Tony; Gardner, J.; Johnston, R.; Payne, C.; Shannon, A.; Ware, B.; Smith, Anne (Churchill Livingstone, 2014)
It has been proposed that patients with chronic non-specific low back pain (CNSLBP) can be broadly classified based on clinical features that represent either predominantly a mechanical pain (MP) or non-mechanical pain (NMP) profile. The aim of this study was to establish if patients with CNSLBP who report features of NMP demonstrate differences in pain thresholds compared to those who report MP characteristics and pain-free controls. This study was a cross-sectional design investigating whether pressure pain threshold (PPT) and/or cold pain threshold (CPT) at three anatomical locations differed between patients with mechanical CNSLBP (n= 17) versus non-mechanical CNSLBP (n= 19 and healthy controls (n= 19) whilst controlling for confounders. The results of this study provide evidence of increased CPT at the wrist in the NMP profile group compared to both the MP profile and control subjects, when controlling for gender, sleep and depression (NMP versus MP group Odds Ratio (OR): 18.4, 95% confidence interval (CI): 2.5-133.1, p= 0.004). There was no evidence of lowered PPT at any site after adjustment for confounding factors. Those with an MP profile had similar pain thresholds to pain-free controls, whereas the NMP profile group demonstrated elevated CPT’s consistent with central amplification of pain. These findings may represent different pain mechanisms associated with these patient profiles and may have implications for targeted management.